Meningkatkan Kemampuan Berpikir Spasial dengan Model Discovery Learning pada Pembelajaran Geografi - Virgiawan, Dhimas Bagus; Murtini, Sri; Rahmah, Ririn Ra'ifatur (ASANKA : Journal of Social Science and Education, 2023)
ABSTRACTSpatial thinking skills are needed for students in following the geography learning process. This is aims to improve the ability think spatially with the Discovery Learning model in Geography learning. This is a type of Classroom Action Research at quantitative descriptive analysis which aims to improve the learning process from current conditions to expected conditions. The research was conducted at SMA N 13 Surabaya with the research object being class X-4 with 30 students. The class action research cycle is carried out twice with one face-to-face meeting each. Data collection techniques use observation, projects, and documentation consisting of teaching modules, attendance, and pictures of learning activities. The observation sheet is guided by the PPL 2 PPG Pre-service observation rubric. The conclusion is that there is an increasse the spatial abilities of students through the application of the discovery learning modelKecapakan berpikir spasial diperlukan bagi siswa/i untuk melaksanakan kegiatan belajar di kelas. Tujuan dari penelitian ini meningkatkan kemapuan berpikir spasial dengan model Discovery Learning pada pembelejaran Geografi. Penelitian Tindakan Kelas ini menggunakan analisis deskriptif kuantitatif. Penelitian dilaksanakan di SMA N 13 Surabaya dengan objek penelitian adalah kelas X-4 sebanyak 30 peserta didik. Siklus penelitian ini berjumlah dua siklus. Pengumpulan data dengan cara: observasi, proyek, dan dokumentasi yang terdiri dari modul ajar, presensi, dan gambar kegiatan pembelajaran. Lembar observasi berpedoman pada rubrik observasi PPL 2 PPG Prajabatan.. Kesimpulan adalah terjadi kenaikan tingkat keterampilan berpikir spasial peserta didik dengan model discovery learning